Panoramic view of Boston, ca. 1955-65 - Boston Redevelopment Authority (Tufts Archival Research Center, 2005)
Elevated view looking north from the Suffolk Country Courthouse building. In the center of the image is the New England Telephone building at 10 Cambridge Street, to the left, Bowdoin Square. Chardon Street starts at Bowdoin Square and continues to the right side of the image. Boston Garden and North Station can be seen in the upper right hand corner of the photograph. 7 9/16 x 9 1/2 overall 8 1/16 x 10 Photographs